Atividade antifúngica do óleo essencial de Thymus vulgaris L. e fitoconstituintes contra Rhizopus oryzae e Rhizopus microsporus: interação com ergosterol - Mota, Kelly Samara de Lira (2014)
Mucormycoses are infections that have high rates of morbidity and mortality. They show high resistance to antifungal agents, and there is a limited therapeutic arsenal currently available, therefore, there is a great need to give priority to testing therapeutic agents for the treatment of mucormycosis. Along this line, the use of essential oils and phytoconstituents has been emphasized as a new therapeutic approach. The objective of this work was to investigate the antifungal activity of the essential oil (EO) of Thymus vulgaris, and its constituents thymol and p-cymene against Rhizopus oryzae and Rhizopus microsporus, through microbiological screening, determination of minimal inhibitory concentration (MICs) and minimal fungicidal concentration (MFCs), effects on mycelial growth and germination of sporangiospores, fungal morphology and interaction with ergosterol. Also was evaluated the preclinical acute toxicity in mice. In microbiological screening the T. vulgaris essential oil showed antifungal potential against resistant strains of R. oryzae.The MIC of EO and thymol varied 128 512 μg/mL, but the MFC of EO and thymol varied 512 1024 μg/mL and 128 1024 μg/mL, respectively. The results also showed that EO and thymol significantly inhibited mycelial development and germination of sporangiospores of both species of Rhizopus. Investigation of the mechanism of antifungal action showed that EO and thymol interact with ergosterol. These data indicate that EO of T. vulgaris and thymol possess strong antifungal activity, which can be related to their interaction with ergosterol, supporting the possible use of these products in the treatment of mucormycosis. In preclinical acute toxicology the doses of 125, 250, 500 and 1000 mg/kg intraperitoneally (i.p.) showed depressive activity on the central nervous system (CNS). In addition to these parameters was observed that the doses of 125 and 250 mg/kg did not change the body and organs weight of the animals, but it was observed change some of the hematological parameters of the mice. The EO showed DL50 of 250 mg/kg for male and 459.6 mg/kg for female; however the thymol showed DL50 of 222.3 mg/kg for male and 1551 mg/kg for female. These data indicate that EO of T. vulgaris and thymol possess strong antifungal activity, which can be related to their interaction with ergosterol.